Temperament and character traits in patients with anorectal disorder - Akçay, Bülent Devrim; Gül, Vahit Onur; Özer, Serhat (Journal of Surgery and Medicine, 2018)
Aim: The aim of this cross-sectional study is to investigate temperament and character traits in patients with anorectal disorders, considering that temperament and character traits of patients with anorectal disorders will be affected differently from healthy individuals. Methods: We compared 102 patients diagnosed with one of the four most common anorectal disorders (hemorrhoidal disease, anal fissure, anorectal abscess/fistulae, and sacrococcygeal pilonidal disease) who applied to the out-patient clinic and 80 healthy adults without any medical condition. Both groups were administered sociodemographic and descriptive information questionnaire, Temperament and Character Scale (TCS), Beck Depression Scale (BDI), Beck Anxiety Scale (BAI) and State and Trait Anxiety Scale (STAI). Results: According to the control group, the patients with anorectal disorders had higher harm avoidance (HA) scores from temperament dimensions and lower self-directedness (SD) scores from character dimensions. The anxiety and depression rates were higher in the group with anorectal disorders. Conclusions: Anorectal disorders are common diseases in the society. Temperament and character traits are closely related to comorbid psychiatric disorders seen in patients with anorectal region disease. At the same time temperament and character traits can affect compliance with medical and surgical interventions for anorectal disease. Our study has provided important data to encourage clinicians to evaluate patients in a multidisciplinary approach in the treatment of anorectal disorders that are generally predisposed to chronicity.